Silver nanoparticles in sewage treatment plant effluents: chronic effects and accumulation of silver in the freshwater amphipod Hyalella azteca - Kühr, Sebastian (Environ Sci Eur, 2018)
BACKGROUND: Increasing amounts of engineered nanoparticles (NPs) in wastewater can reach the aquatic environment by passing through the sewage treatment plant (STP). NPs can induce ecotoxicological effects due to their specific chemical properties. However, their bioavailability and toxicity are potentially influenced by transformation processes caused by substances present in the STP, e.g., humic acids or sulfides. Due to the lack of a test system allowing to test NPs under realistic environmental conditions, we coupled two existing test systems, the activated sludge simulation test (OECD TG 303A 2001) and the chronic exposure test with the freshwater amphipod Hyalella azteca (Environment Canada 2013), to gain a test scenario that allows to consider the altered behavior and fate of NPs induced by the STP process. This should improve the environmental realism of the chronic exposure test with Hyalella. In the first study, we tested the STP effluent containing AgNPs. In the second and third study, tap water and control STP effluent were spiked with AgNPs and used as test media. RESULTS: The chronic exposure studies with the freshwater amphipod H. azteca showed that the investigated AgNPs lose most of their toxicity while passing through the STP. Over all studies with total Ag concentrations ranging from 0.85 to 68.70 µg/L, significant effects of the AgNPs were only observed in the survival of test animals exposed to tap water containing the highest Ag concentration (62.59 µg/L). Accumulation of silver in the body of test animals was clearly dependent on the pretreatment of the AgNPs. Silver ions (Ag(+)) released from AgNPs are supposed to be the major pathway leading to body burden following exposure to test media containing AgNPs. CONCLUSION: The coupled test system is suitable for testing substances that can reach the environment via the STP effluent. The investigated AgNPs lose most of their toxicity while passing through the STP. Accumulation of silver in the animals exposed to the different treatments was apparent, whereby silver ions (Ag(+)) released from AgNPs were supposed to be the major pathway leading to body burden.